Age group training - Stacy, R. (American Swimming Magazine, 1998)
The thesis of this article is quite simple: young age group swimmers, those 8 to 10 years old, should be in a program that emphasizes stroke technique and a solid base of aerobic conditioning. This is not a plea for unlimited or mindless yardage for young swimmers. But it is a suggestion that guidelines for young swimmers in recent years have been too inflexible and understate the amount of work that young swimmers can and should be doing in order to develop to their full potential as senior swimmers. On endurance training as the core of the Lake Erie Silver Dolphin team philosophy. In summary, we believe that an age group program should emphasize a strong component of technique work and aerobic conditioning. Although not an open-ended quest for yardage, young swimmers should be progressively presented with challenging workouts that develop their aerobic systems. We believe that such a program benefits young swimmers both physically and mentally, and that it best prepares them for longer and more successful careers as senior swimmers. A sample of workouts is offered for this age group.